Ambivalent enmity and adolescence in a wartime diary (1941-1944): historical and psychological perspectives - Penter, Tanja; Taubner, Svenja (The journal of transcultural studies, 2023)
This article evaluates the diary of Olga Kravtsova, a young Ukrainian woman who documented her experiences, thoughts, and feelings almost daily from 1941 to 1944. The diary reveals a young person shaped by Stalinism who, amid the crises and conflicts of adolescence, experienced the horror of the German war of extermination and occupation in Ukraine and the purges in the first months after the return of Soviet rule. Olga describes her ambivalent feelings towards the German occupiers, which gradually transformed from hostility, to friendship, and even to romantic attachment. Our interdisciplinary approach to this material, which combines the perspectives of history and psychology, allows for a greater and more sympathetic awareness of historical and cultural conditions and expands the disciplinary boundaries of both scholarly fields. In addition, our reading of Olga’s diary additionally reveals the inherent ambivalence of enmity. It sharpens our view of the phenomenon of collaboration, cooperation with the enemy, and invites the reader to become more aware of the contingency, relationality, and processuality of enmity relations.
Gesehen am 04.06.2024